IMPLEMENTASI ZAKAT PRODUKTIF TERHADAP PENGENTASAN KEMISKINAN DI BAZNAS KABUPATEN SITUBONDO - Fitria Desi Nuri Cahyani; Muhammad Dhofir Catur Bashori; Istikomah (I'THISOM : Jurnal Ekonomi Syariah, 2025)
Zakat is a vital instrument in the Islamic economic system, aimed at promoting social justice and reducing economic inequality. In regions with high poverty rates, productive zakat serves as an alternative strategy to help mustahik (zakat recipients) achieve sustainable economic improvement. The National Amil Zakat Agency (BAZNAS) of Situbondo Regency actively implements productive zakat through various community economic empowerment programs. This study aims to examine (1) how productive zakat is implemented by BAZNAS Situbondo to improve the economic conditions of mustahik and (2) the supporting and inhibiting factors affecting its effectiveness as a poverty alleviation instrument. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation. Informants included BAZNAS managers and mustahik who received productive zakat. Data analysis involved data reduction, presentation, and conclusion drawing. The findings indicate that productive zakat positively impacts mustahik’s economic conditions, including increased income, improved business independence, and reduced reliance on social assistance. Programs such as small business capital assistance and skills training are essential components of the economic empowerment strategy. Supporting factors include the commitment of BAZNAS managers, active community participation, and collaboration with other institutions. Inhibiting factors comprise limited zakat funds, insufficient continuous assistance, and low financial literacy among mustahik. In conclusion, productive zakat is an effective instrument for poverty alleviation when managed in a targeted and sustainable manner, with active involvement from all relevant stakeholders. The program demonstrates that zakat, when combined with guidance and empowerment strategies, can foster long-term economic resilience among recipients.